2018
DOI: 10.1155/2018/9680184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Microwave Power on Extraction Kinetic of Anthocyanin from Blueberry Powder considering Absorption of Microwave Energy

Abstract: Microwave power as directly controlled parameter determines the absorption of microwave energy inside extraction vial and the yield of objective component in microwave-assisted extraction (MAE). The aim of this study was to elucidate the effects of microwave powers on the yield of anthocyanin from blueberry (Vaccinium spp.) powder based on the absorption of microwave energy in extracts under MAE. Rising microwave powers have little effect on the distribution of microwave energy in extraction vial, but increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The influence of 10 mmol/L K + and Cu 2+ on the anthocyanin retention rate was relatively low, and when their concentrations increased to 20 mmol/L, there was no obvious decrease; however, Fe 2+ addition at 10 mmol/L and 20 mmol/L showed notable and similar decreases in anthocyanin retention. Xue et al (2018) found that under microwave-assisted extraction conditions, the critical extraction temperature for optimum anthocyanin yield confirmed that light has a very adverse effect on the stability of anthocyanins during storage. High oxygen contents can lead to a decrease in anthocyanin contents because anthocyanins inhibit radical activity at high oxygen concentrations, causing depletion of the antioxidant pigments (Gustavo et al,2009).…”
Section: The Influence Of Different Storage Conditions On Blueberry Anthocyanin Stabilitymentioning
confidence: 84%
“…The influence of 10 mmol/L K + and Cu 2+ on the anthocyanin retention rate was relatively low, and when their concentrations increased to 20 mmol/L, there was no obvious decrease; however, Fe 2+ addition at 10 mmol/L and 20 mmol/L showed notable and similar decreases in anthocyanin retention. Xue et al (2018) found that under microwave-assisted extraction conditions, the critical extraction temperature for optimum anthocyanin yield confirmed that light has a very adverse effect on the stability of anthocyanins during storage. High oxygen contents can lead to a decrease in anthocyanin contents because anthocyanins inhibit radical activity at high oxygen concentrations, causing depletion of the antioxidant pigments (Gustavo et al,2009).…”
Section: The Influence Of Different Storage Conditions On Blueberry Anthocyanin Stabilitymentioning
confidence: 84%
“…Inc.). 19.67 to 24.41; 8.31 to 13.12 and 2.766 to 4.116 mg/g, respectively. Maximum extractable total phenolics were recorded in flower extract from Borije (54.45 mg GAE/g) followed by flower extract from Vareš (44.41).…”
Section: Antimicrobial Activity Detection By Agar Well Diffusion Methodmentioning
confidence: 96%
“…Microwave (MW) is another innovative and green extraction technology considered to be more advantageous than conventional extraction technologies due to its high extraction rate, less use of solvents, and shorter extraction time [ 109 ]. Anthocyanins from different plant sources have been successfully extracted by using MW technology [ 116 , 117 , 118 , 119 , 120 ]. MW technology enhanced anthocyanin extraction from various agri-food by-products compared to conventional extraction technologies or even other innovative extraction technologies (e.g., US) (for more details, see Table 3 ).…”
Section: Innovative Processes For Anthocyanin Extraction From Agri-food By-productsmentioning
confidence: 99%
“…In addition to solvent, microwave power, irradiation time, and extraction temperature also significantly impact the performance of MW extraction [ 132 ]. Overall, cell structure disintegration intensifies as the intensity of these parameters increases, thereby improving the extraction yields of target compounds [ 119 ]. Indeed, several studies conducted with MW have shown an increase in anthocyanin extraction from agri-food by-products as these parameters are intensified.…”
Section: Innovative Processes For Anthocyanin Extraction From Agri-food By-productsmentioning
confidence: 99%